Minecraft Wither Without You - 3 3 / Wither without you. - Gudsnuk, Kristen (Milwaukie, OR : Dark Horse Books, 2022)
"After surviving the horrors of a zombie villager outbreak, the adventurers begin to make their way to Atria's hometown of Woodhaven. But the journey is far from a smooth one, and dangers lurk around every corner, as our heroes witness more evidence of the Wither's path of destruction across the overworld. With new allies at their side and an arsenal of magic at their disposal, Senan, Cahira, Orion, Atria, and Wilkie prepare themselves for the final explosive confrontation with the fearsome creature. But are they a match for the mysterious Wither? "--Provided by publisher.
Keywords: Minecraft (Game) -- Comic books, strips, etc; Twins -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Search and rescue operations -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Minecraft (Game) -- Fiction; Twins -- Fiction; Magic -- Fiction; Monsters -- Fiction; Search and rescue operations -- Fiction; Quests (Expeditions) -- Fiction; Graphic novels; Comics (Graphic works)